Research progress of piezoelectric materials in protecting oral health and treating oral diseases: a mini-review - Yang, Tingyu; Sa, Rina; Wang, Furong; Chen, Chen; Zheng, Lanbing (Frontiers in Bioengineering and Biotechnology, 2024)
Piezoelectric materials, as a class of materials capable of generating electrical charges under mechanical vibration, have special piezoelectric effects and have been widely applied in various disease treatment fields. People generate vibrations in the oral cavity during daily activities such as brushing teeth, using electric toothbrushes, chewing, and speaking. These natural vibrations (or external ultrasound) provide ideal conditions for activating piezoelectric materials, leading to their high potential applications in protecting oral health and treating oral diseases. Based on this, this review reports on the research progress and trends of piezoelectric materials in the protection of oral health and the treatment of oral diseases in the past five years, and discusses its treatment mechanism, challenges and shortcomings, aiming to provide theoretical basis and new ideas for the future application of piezoelectric materials in the field of oral cavity. Finally, a brief outlook is provided, suggesting that the potential of piezoelectric materials may enable them to quickly move towards real clinical applications.